The Synthesis of New Thermal Stable Schiff Base/Ester Liquid Crystals: A Computational, Mesomorphic, and Optical Study - Mohamed Hagar; Hoda A. Ahmed; Sherif S. Nafee; Reda M. El-Shishtawy; Bahaaudin M. Raffah (Molecules, 2019)
A Schiff base supramolecular 4-[(4-(hexyloxy)phenylimino)methyl]benzoic acid and a new series of Schiff base/ester linkages named 4-substitutedphenyl 4-[(4-(hexyloxy)phenylimino)methyl]benzoate liquid crystals were synthesized. The thermal stability, mesomorphic, and optical behavior of the prepared compounds were characterized by differential scanning calorimetry (DSC), Thermogravemetric analysis (TGA), polarized optical microscopy (POM), and UV spectroscopy. FT-IR, 1H-NMR, 13C-NMR, and elemental analyses were carried out to elucidate and confirm the molecular structures of the synthesized compounds. The investigated series comprising different sized terminal polar groups changed between CH(CH3)2, H, I, and F. It was found that the supramolecular imino acid dimer is enantiotropic dimorphic, with a wide SmA phase and a good N phase range. The other series of terminally substituted Schiff base/esters are mesomorphic with a high thermal stable SmA phase, except the iodo derivative, which showed dimorphic SmA and N phases. The effect of the position and the orientation of the cores, as well as the terminal substituent of the type and the stability of the mesophase, were studied. A computational theoretical study of the effects of the van der Waal’s volume, the Hammett substituent coefficient, the inductive sigma constant, and other geometrical parameters were discussed. The study revealed that the planarity of the two phenyl rings attached with an imino linking group impacted the resonance effect of the terminal substituents rather than their inductive effect. A detailed study on the effect of the estimated thermal parameters, as well as their geometrical planarity with the type and stability of the formed mesophase, was discussed.